Cultural representation of Chinese elements in Genshin impact and its influence on player interest - Marina Wardaya (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
This study was conducted by using different ways to analyse participant interest through combining qualitative methods that looked at Culture from Traditional Chinese Society and how that reflects on Genshin Impact and Quantitative Methods to determine the overall influence of Culture from Traditional Chinese Society and Genshin Impact. Through this approach, our focus was the visual representations of Lions from Lion Dance Tradition within Genshin Impact, and how these images contrasted to both the narrative storyline and environmental aspects associated with Chinese Culture. Quantitative data were collected through a survey of 65 players to measure their perceptions, interest levels, and engagement with the cultural representations presented in the game. Qualitative analysis was conducted through visual and content analysis of character design, narrative context, and game mechanics to identify how Chinese cultural elements are constructed and communicated. The findings from this mixed methods approach indicate that the visual and narrative representation of Chinese culture in Genshin Impact positively influences player interest and stimulates curiosity about the cultural themes depicted in the game. These results suggest that digital games have the potential to serve as effective media for introducing cultural representation through immersive visual and interactive experiences.